Beyond oil and gas : the methanol economy - 365814 Olah, George A. (George Andrew), 1927-; Goeppert, Alain, 1974-; Prakash, G. K. Surya (Weinheim : Wiley-VCH, 2009)
Includes bilbiographical references (p. 297-326) and index